THE CULTURE OF THE INFORMATIONAL SOCIETY. THEORETICAL DISCOURSE OF POLITICAL COMMUNICATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article considers the issue of “informational society”, in which communicationis the basis for the activities of political scientists, sociologists, philologists, culturologists, psychologists, historians and cyberneticians and other scientists who have devoted their research to theissue of humanities disciplines. The possibility of reflexion prompts the author to refer to them asdisciplines within the zone of influence of communicativism. Therefore, there is nothing surprising, for example, in the emergence of the concept of “information society”, which arises only onthe basis of the intersection of the two original concepts - society and information.
Keywords: informational society, digital literacy, mass communication, political communication, media culture, civic engagement, communitivistics, framing, media